Dissecting Indonesian Insurance Profitability and Efficiency: Du Pont Diagnostic Tool. - Guntur Tri Hidayatulloh; Dyah Palupiningtyas; Tri Maryani (Universitas Sains dan Teknologi Komputer, 2024)
This research compares the financial performance of insurance companies in Indonesia using the Du Pont method, identifies the determinants of differences in profitability and efficiency, and provides strategic recommendations. The methodology involves analyzing the 2023 audited financial statements of PT Asuransi Dayin Mitra Tbk and PT Asuransi Bintang Tbk as samples, applying the Du Pont method, financial ratios, and qualitative analysis. The results reveal a significant difference in profitability, with PT Asuransi Dayin Mitra Tbk excelling in net profit margin, asset turnover, and a conservative capital structure, while PT Asuransi Bintang Tbk outperforms in underwriting risk management, claims handling, and aggressive marketing strategies. Strategic recommendations include maintaining strengths, exploring revenue growth, enhancing cost efficiency, and adjusting capital structure. This research contributes to understanding the dynamics of financial performance in the Indonesian insurance industry.